Reduced MIBG accumulation of the parotid and submandibular glands in idiopathic Parkinson's disease. (January 2017) - Haqparwar, Jaweed; Pepe, Antonio; Fassbender, Klaus; Dillmann, Ulrich; Ezziddin, Samer; Schaefer, Andrea; Leppert, Daniela; Spiegel, Jörg
Abstract: Introduction: Alpha-synuclein pathology (ASP) is a characteristic histopathological finding in idiopathic Parkinson's disease (PD). The ASP involves not only the brain but also extracranial structures. In the present study we utilized MIBG scintigraphy to measure the sympathetic innervation of the major salivary glands. We were interested in whether MIBG uptake in the major salivary glands represents a potential biomarker for ASP in PD. Methods: We investigated 77 PD patients (age 61 ± 10 years, mean ± SD), while 15 non-PD patients (age 58 ± 15 years) with arterial hypertension, who underwent MIBG scintigraphy to exclude pheochromocytoma, served as age-matched controls. The MIBG uptake of the parotid glands and the submandibular glands was quantified by means of a region of interest technique. The sublingual glands were too small for an exact measurement. We applied Generalized Estimating Equations (GEE) to identify and remove factors which may bias the statistical correlation analysis. Results: The PD patients showed a significantly lower MIBG uptake in the parotid and submandibular glands than the controls (p < 0.0001). MIBG uptake in the PD patients did not correlate with clinical severity (Hoehn and Yahr stage, motor part of the UPDRS) or disease duration. Conclusion: MIBG uptake in the parotid and submandibular glands might be a candidate biomarker for PD. The missing correlation between MIBG uptake and clinical PD parameters suggests that ASP of the extracranial sympathetic superior cervical ganglion, which innervates the major salivary glands, develops independently from the cerebral dopaminergic nigrostriatal ASP. Highlights: MIBG scintigraphy may quantify MIBG uptake of parotid and submandibular glands. PD patients showed a reduced MIBG uptake in these salivary glands. A reduced MIBG uptake of these salivary glands might be a biomarker for PD. The MIBG uptake does not correlate with clinical symptoms of PD.